Forma??o de professores do Ensino Superior: uma an?lise do programa institucional de desenvolvimento profissional docente da Universidade Estadual de Feira de Santana ? UEFS - Silva, Daniella Oliveira da (2024)
This dissertation research, entitled ?Teacher Training in Higher Education: an analysis of the professional development program for teachers at the State University of Feira de Santana - BA?, has the general objective of investigating the implications of the implementation of the institutional teacher training policy (ProFACE ) from the State University of Feira de Santana (UEFS) for the construction of didactic-pedagogical knowledge, and consequent professional development of university teachers. The central question reveals our interest in characterizing and analyzing the institutional policy implemented at UEFS, ProFace, through documents (printed and digital), questionnaires and interviews, regarding: organization, objectives, evaluation and implications of the implementation of the policy institutional for the construction/mobilization of didactic-pedagogical knowledge, and consequent professional development of university teachers. The theoretical framework is dedicated to themes related to the training and professional development of Higher Education teachers, as well as University Pedagogy programs in Brazil. This is a qualitative research, Case Study type, with a qualitative approach. The locus of the investigation was UEFS and the collaborating subjects were the team members and general coordinators of the Academic Training and Contextualization of Educational Experiences Program - ProFACE. The instruments chosen for data production were the questionnaire and the semi-structured interview. To analyze the data, we were inspired by the content analysis proposed by Bardin (1997), which revealed categories of analysis that enabled the investigation of the object of study. The data collected revealed that ProFACE was born from an institutional effort, but not from the entire community. Data analysis identified that it is a University Pedagogy Program that seeks to contribute to the proposition of institutional policies for teacher training and teaching professional development, especially Didactic-Pedagogical training. The institution, locus of investigation, continuously develops teacher training through workshops, actions, programs and training spaces, tensioned by the absence of public policies that actually consider and value Higher Education teachers, in the exercise of their profession. To identify themes, the focus of the program's actions, the process of continuous listening to the needs of teachers stands out, based on activities structured by the program group and collective reflection on themes that are present in the practices developed in the institution's daily life. , many of which have also been identified by other research, primarily those developed by the Group of Studies and Research in University Pedagogy - NEPPU, especially the work that deals with teachers who work in the investigated institution. The research carried out suggests that in these spaces and programs, the The relationships between training and professional development do not yet have a defined identity, as a concrete reality. It also revealed that the institutional program investigated focuses a large part of its actions on institutional needs and gaps in teacher training. Furthermore, the institution still does not guarantee that the program is, in fact, institutional and that it fits into the teaching career. The research reinforces the need to institutionalize training proposals as an institutional policy, guaranteed in institutional regulations that ensure their continuity and permanence, not only as specific actions, but, above all, a policy that values the professional trajectory of teachers, with support and recognition of their professional activities and, going further, opening spaces for critical reflection on what they do to be a driving force for doing university together, collectively.